Understanding the Macroscopic, Microscopic, and Symbolic Levels of Angiosperms through SiMaYang Type II Learning - Alkham, Fithri Fakhrunnisa; Haryani, Sri; Ridlo, Saiful (Universitas Negeri Semarang)
This study aims to analyze the effectiveness of the Si-Lima Layang-layang (SiMaYang) type II learning model on Angiosperms material on understanding the macroscopic, microscopic, and symbolic levels. This study was a pretest-posttest multiple group design experiment. The effectiveness of the learning model was measured by the N-gain score of the angiosperm test. Hyphothesis was tested using Manova (Multivariate Analysis of Variance) with SPSS. The result of the analysis is the sig value. 0.010 < 0.05, which means that there is a significant difference in understanding the macroscopic level between the SiMaYang type II class and the Discovery Learning class. Sig value. 0.016 < 0.05, which means that there is a significant difference in understanding microscopic level between the SiMaYang type II class and the Discovery Learning class. Sig value. 0.396 > 0.05, which means that no significant difference level of understanding the symbolic between the SiMaYang type II class and the Discovery Learning class. It can be concluded, SiMaYang type II is effective in improving understanding at the macroscopic and microscopic level, but not for the symbolic.